Prevalence of psychiatric morbidity in elderly hospitalized patients - Aslam Khan; Pooja Vijay; A V Sowmya; Suprakash Chaudhury; Bhushan Chaudhari; Daniel Saldanha; Preethi Menon (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Background: Improved healthcare extends life expectancy, but social and economic issues including poverty, family breakdown, and insufficient help for the elderly put people's mental health in danger. Because of feelings of loneliness and natural age-related decline in physiological and physical performance, the elderly are more prone to psychological disorders. With this aim in mind, the study of the prevalence of psychiatric morbidity in elderly hospitalized patients was taken up. Methods: A cross-sectional analytical study was carried out in a tertiary hospital in Pune on 200 hospitalized patients of 65 years of age and more from July 2019 to July 2021. Subjects with known psychiatric disorders were excluded. Subjects were evaluated with a sociodemographic proforma, mini-international neuropsychiatric interview (MINI), depression anxiety stress scale-21 (DASS-21), and the multidimensional scale of perceived social support (MSPSS). Results: A total of 35.5% of elderly subjects admitted to non-psychiatric wards were found to be suffering from psychiatric disorders, most commonly major depressive disorder, generalized anxiety disorders (GADs), and social anxiety disorders. On DASS-21, 55.5% of patients had stress, 24% anxiety, and 15.5% had depression. On the MSPSS scale, 53% had a high level of support. A mean score of 5.94 was obtained for family support, 5.413 for support from friends, and 3.486 for support from significant others. Males received higher support. Conclusion: We found that elderly patients admitted in non-psychiatric wards had psychiatric disorders. The most common psychiatric disorders were GAD (16.5%) and major depressive disorder (15%). It is more beneficial when physicians/surgeons also screen or refer their elderly patients to their psychiatrist colleagues to help alleviate their suffering to the extent possible.